2018
DOI: 10.1111/jsap.12914
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between brachycephalic airway syndrome and gastrointestinal signs in three breeds of dog

Abstract: The prevalence of gastrointestinal signs in dogs presenting with brachycephalic airway syndrome and improvement in these clinical signs following corrective surgery may vary between breeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 21 publications
9
56
0
Order By: Relevance
“…We did not intend to investigate the management of brachycephalic dogs with BOAS in this study, but dogs of such breeds were significantly more likely to receive omeprazole and maropitant in the Surgery ward for the stated reasons of decreasing the rate and/or consequences of regurgitation and GOR under anaesthesia. Both problems are common in brachycephalic dogs 34,35 , though the prevalence of intra-operative GOR did not differ between brachycephalic and control dogs in a previous study 36 . Regurgitation in brachycephalic dogs is attributed principally to excessive negative pressure in the thorax 37 , but it is unclear whether affected dogs also experience nausea.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We did not intend to investigate the management of brachycephalic dogs with BOAS in this study, but dogs of such breeds were significantly more likely to receive omeprazole and maropitant in the Surgery ward for the stated reasons of decreasing the rate and/or consequences of regurgitation and GOR under anaesthesia. Both problems are common in brachycephalic dogs 34,35 , though the prevalence of intra-operative GOR did not differ between brachycephalic and control dogs in a previous study 36 . Regurgitation in brachycephalic dogs is attributed principally to excessive negative pressure in the thorax 37 , but it is unclear whether affected dogs also experience nausea.…”
Section: Discussionmentioning
confidence: 62%
“…Regurgitation in brachycephalic dogs is attributed principally to excessive negative pressure in the thorax 37 , but it is unclear whether affected dogs also experience nausea. Interestingly, owners reported ptyalism, which is often taken as a sign of nausea, to be much less common in such dogs than regurgitation 34 . Additionally, in our experience, brachycephalic dogs with regurgitation rarely have a decreased appetite, which might be expected if they were experiencing nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with available data, snoring, inspiratory efforts, and exercise intolerance were the most common presenting clinical signs, followed by syncope . Moreover, 76.7% of dogs with respiratory problems also had gastrointestinal clinical signs, specially vomiting and regurgitation . Although it is not frequently described, SDB may be consequence of BAOS .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of granulation tissue with inflammatory infiltrate on histopathology has been suggested to occur in brachycephalic dogs as a sequelae to repetitive micro-trauma secondary to airway collapse and negative upper airway pressures in a study of French bulldogs (Sarran et al 2018). French bulldogs have a high prevalence of regurgitation and vomiting (Kaye et al 2018) and it was suggested that gastro-oesophageal reflux could be a contributing factor as in humans, although this has not specifically investigated in dogs. In contrast, only one French bulldog with an inflammatory lesion (granulation tissue with neutrophilic inflammation) was identified in this study.…”
Section: Discussionmentioning
confidence: 99%